Numerical and Experimental Simulation of Supersonic Gas Outflow into a Low-Density Medium - Kirill Dubrovin; Lev Yarkov; Alexandr Zarvin; Alexander Zaitsev; Valeriy Kalyada; Alexandr Yaskin; Yevgeniy Bondar (Aerospace)
This study is aimed at developing methods for the experimental and numerical simulation of the outflow of underexpanded gas jets into a rarefied medium. The numerical method is based on using Navier–Stokes equations in the continuum flow regime and the direct simulation Monte Carlo method in the transitional flow regime. The experimental method includes the modeling of jet flows in the LEMPUS-2 gas-dynamic setup with electron beam diagnostics for the jet density measurements. The results of the experimental modeling for the nozzles of various diameters confirm that a key parameter determining the jet structure is the Reynolds number based on the characteristic length ReL. The results of the numerical simulations agree well with the experimental data both for the maximum values of the ReL considered (approximately 30) when a barrel jet structure with Mach disks is formed and for the minimum values (approximately 4) when no Mach disks are formed. In the entire range of parameters, significant thermal nonequilibrium is observed at all jet segments where the measurements are performed.